Mapping global value chains : intermediate goods trade and structural change in the world economy - Sturgeon, Timothy J. (UNIDO ViennaAT, 2011)
Looks at world economy. Addresses a small part of the data gap relating to detailed quantification and empirical characterisation, by using novel classifications for final and intermediate goods trade; for "customised" and "generic" intermediate goods; and in the three industries oft-cited as being at the forefront of global economic integration viz, electronics, automobiles and motorcycles and, apparel and footwear.